2009
DOI: 10.1097/ncq.0b013e3181955f30
|View full text |Cite
|
Sign up to set email alerts
|

Are Call Light Use and Response Time Correlated With Inpatient Falls and Inpatient Dissatisfaction?

Abstract: Inpatients use call lights to seek nurses' assistance. Although implied in patient safety, no studies have analyzed data related to the use of or response time to call lights collected by existing tracking mechanisms monitoring nursing practice. This study used archived hospital data to determine the correlation of the call light use rate and the average call light response time with the fall rate, injurious fall rate, and patient satisfaction scores in acute inpatient care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 13 publications
2
31
1
1
Order By: Relevance
“…A significant portion of the call light research and their usage focuses on the device as a tool for patient safety. One study showed that on surgical units, when call light use was high, the patient injurious fall rate was lowered (1) . In the same study, however, medical unit patient fall rates were not significantly related to more frequent use of call lights (1) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A significant portion of the call light research and their usage focuses on the device as a tool for patient safety. One study showed that on surgical units, when call light use was high, the patient injurious fall rate was lowered (1) . In the same study, however, medical unit patient fall rates were not significantly related to more frequent use of call lights (1) .…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that on surgical units, when call light use was high, the patient injurious fall rate was lowered (1) . In the same study, however, medical unit patient fall rates were not significantly related to more frequent use of call lights (1) . Meade and colleagues (7) found that the incorporation of hourly nursing rounds on nursing units lead to both a decreased use of call lights and a decreased patient falls by anticipating patients' needs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, previous work has examined how to reduce the number of interruptions, for example, through the introduction of additional nursing rounds [4,11]. Contradictorily, although there could be other factors involved, Tzeng and Yin [12] found that departments with the most frequent use of nurse calls had the fewest fall rates and the highest patient satisfaction score, encouraging the use of nurse calls among patients.…”
Section: Introductionmentioning
confidence: 96%